Faecal immunochemical testing for haemoglobin in detecting bowel polyps in symptomatic patients: multicentre prospective cohort study. Issue 2 (8th March 2023) - Bath, Michael F; Malhi, Aman; Ayling, Ruth M; Seward, Edward; Pritchard-Jones, Kathy; Laszlo, Helga E; Hackshaw, Allan; Machesney, Michael R
Abstract: Background: Measurement of faecal haemoglobin using faecal immunochemistry testing is recommended in patients presenting with symptoms suspicious for colorectal cancer, to aid in triage and prioritization of definitive investigations. While its role in colorectal cancer has been extensively investigated, the ability of faecal immunochemistry testing to detect adenomas in symptomatic patients is unclear. Methods: A multicentre prospective observational study was conducted between April 2017 and March 2019, recruiting adults from 24 hospitals across England and 59 general practices in London who had been urgently referred with suspected colorectal cancer symptoms. Each patient provided a stool sample for faecal immunochemistry testing, in parallel with definitive investigation. A final diagnosis for each patient was recorded, including the presence, size, histology, and risk type of colonic polyps. The outcome of interest was the sensitivity of faecal immunochemistry testing in detecting the presence of adenomas. Results: Of 3496 patients included in the analysis, 553 (15.8 per cent) had polyps diagnosed. Sensitivity of faecal immunochemistry testing for polyp detection was low across all ranges; with a cut-off for faecal haemoglobin of 4 µg/g or lower, sensitivity was 34.9 per cent and 46.8 per cent for all polyp types and high-risk polyps respectively. The area under the receiver operating characteristic curve in detection probability was relatively low for both intermediate-risk (0.63) and high-risk polyps (0.63). Conclusion: While faecal immunochemistry testing may be useful in prioritizing investigations to diagnose colorectal cancer, if used as a sole test, the majority of polyps would be missed and the opportunity to prevent progression to colorectal cancer may be lost. Abstract : Faecal immunochemistry testing (FIT) is currently used in the UK to triage patients referred with symptoms suggestive of colorectal cancer; however, the role of FIT in the detection of adenomatous polyps, a known precursor to colorectal cancer, in symptomatic patients is unknown. Our study demonstrates that if FIT were used as a triage for further investigations in symptomatic patients, more than half of all high-risk adenomas would be missed, therefore current endoscopic investigations in symptomatic patients must remain to ensure that all adenomas can be identified and removed.